Application of Laser in Oral Surgery - Asnaashari, Mohammad; Zadsirjan, Saeede (Journal of Lasers in Medical Sciences, 2014)
In this review collected from the literature on usage of laser in oral minor surgery based on a Medline search in the time period between the years: 2008 and 2013, the most current evidence on laser-assisted oral minor surgery is going to be surveyed.